Do job resources buffer the harmful effects of job demands on burnout complaints? A 1-year cohort study of Swedish healthcare professionals - Britta E Gynning; Elin Karlsson; Kevin Teoh; Per Gustavsson; Filip Christiansen; Emma Brulin (International Journal of Nursing Studies Advances)
Background: The job demands-resources model posits that job resources buffer the effects of job demands on subsequent strain. However, empirical support for this is inconclusive, with some studies suggesting this may be context- or even profession-specific. Objective: To investigate the buffering effect in the job demands-resources model within the Swedish healthcare sector and the impact of professional differences on this effect Method: Data were drawn from a 1-year cohort called the Longitudinal occupational health survey for healthcare in Sweden, utilising the 2022 and 2023 waves. The study sample consisted of Swedish healthcare professionals who at baseline were 69 years or younger, who participated in both survey waves. In total, the study included 4132 healthcare professionals (1649 physicians, 1631 registered nurses, and 852 nurse assistants). Descriptive statistics and ordinary least squares regression moderation analysis were carried out. Results: The experience of control at work buffered the impact of several job demands, including quantitative demands (Beta coefficients [B] =−0.034, 95 % confidence interval [CI] [−0.05; −0.01]), illegitimate work tasks (B=−0.018, 95 % CI [−0.04;−0.01]), effort-reward imbalance (B = −0.050, 95 % CI [−0.08; −0.01]), and work-life Interference (B = −0.023, 95 % CI [−0.04; −0.004]) on subsequent burnout complaints. Collegial support buffered the effect of emotional demands (B = −0.025, 95 % CI [−0.04; −0.01]). Physicians reported a greater buffering effect from control compared with nurse assistants on the effect of illegitimate work tasks (B = 0.084, 95 % CI [0.01;0.16]) and effort reward imbalance (B = 0.120, 95 % CI [0.02;0.22]) towards subsequent burnout complaints. Conclusions: We have contributed to the application of the job demands-resources model by emphasising the critical role of the type of profession in the buffering effect of resources. We have underlined the importance of profession-specific job demands and resources in understanding burnout among Swedish healthcare professionals and in other settings.